2015
DOI: 10.1016/j.cellsig.2015.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen contributes to regulating iron metabolism through governing ferroportin signaling via an estrogen response element

Abstract: Ferroportin (FPN) is the only known iron exporter in mammalian cells, and is universally expressed in most types of cells. FPN signaling plays a crucial role in maintaining iron homeostasis through governing the level of intracellular iron. Serum iron storage is conversely related with the estrogen level in the female bodies, and women in post-menopause are possibly subjected to iron retention. However, the potential effects of estrogen on iron metabolism are not clearly understood. Here, FPN mRNA transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 66 publications
(102 reference statements)
2
32
2
Order By: Relevance
“…Inconsistent with these findings however was the observation that E2 suppresses FPN expression [43] and that it enhances hepcidin synthesis though a GPR30-BMP6-depeddent signaling in hepatocytes and the liver-derived Hep2 cells [44]. This is in direct conflict with previous work, which has shown that elevated levels of E2 associate with increased FPN expression [12].…”
Section: Discussioncontrasting
confidence: 56%
“…Inconsistent with these findings however was the observation that E2 suppresses FPN expression [43] and that it enhances hepcidin synthesis though a GPR30-BMP6-depeddent signaling in hepatocytes and the liver-derived Hep2 cells [44]. This is in direct conflict with previous work, which has shown that elevated levels of E2 associate with increased FPN expression [12].…”
Section: Discussioncontrasting
confidence: 56%
“…Estrogen may influence iron metabolism by modulating the hepcidin-ferroportin axis, which fundamentally governs global iron absorption, distribution, utilization and egress. A repression of ferroportin at the transcriptional level by estrogen was observed in another study and could result in intracellular iron accumulation (66, 67). …”
Section: Discussionmentioning
confidence: 72%
“…Additionally, transcriptional regulation of ferroportin could be studied in more detail using bioinformatics analyses of promoter sequence motifs and reporter gene assays in cell culture. Several transcription factors have been implicated in transcriptional regulation of ferroportin, including hypoxia inducible factor 2 (HIF2 α ), nuclear factor erythroid (Nrf2), metal-regulatory transcription factor 1 (MTF-1) and estrogen receptor [76]. Identification of the regulatory mechanisms that predominate in vivo would allow interfering with transcriptional regulation of ferroportin during inflammation and hence lead to a better understanding of its importance in inflammation, host-pathogen interactions and cancer.…”
Section: Discussionmentioning
confidence: 99%